Application of bacterial cellulose in skin and bone tissue engineering. (5th January 2020) - Pang, Mujuan; Huang, Yinghong; Meng, Fansu; Zhuang, Yong; Liu, Hui; Du, Manling; Ma, Qianqian; Wang, Qi; Chen, Zhen; Chen, Lianyu; Cai, Tiange; Cai, Yu
Graphical abstract: Abstract: Bacterial cellulose (BC) produced by aerobic bacteria has the advantages of high purity, high porosity, strong water absorption, high water holding capacity, high mechanical strength and good biocompatibility. In this review, we briefly introduced the characteristics of BC and the production and modification methods of BC, and focused on the application of BC in skin tissue and bone tissue engineering. At the same time, we summarized the role of BC as a wound dressing and bone repair material in wound healing and bone repair, and prospects for the application of BC as a wound dressing and bone repair material.